Targeting the epidermal growth factor receptor in non-small cell lung cancer - Steins, Martin; Reinmuth, Niels; Bischoff, Helge; Kindermann, Markus; Thomas, Michael (Onkologie, 2010)
The epidermal growth factor receptor (EGFR) has been implicated in a multiplicity of cancer-related signal transduction pathways like cellular proliferation, adhesion, migration, neoangiogenesis and apoptosis inhibition, all of them important features of cancerogenesis and tumour progression. The inhibition of this receptor has been discovered as a suitable pharmaceutical intervention aimed at interrupting tumour activity. In cancer, both monoclonal antibodies and small molecules with anti-tyrosine kinase activity have been assessed in several trials with significant efficacy in clinical applications. The current review focuses in particular on the clinical data of EGFR inhibition in non-small cell lung cancer with emphasis on tyrosine kinase inhibition.